Risk Indicators for Missing Teeth in Working-Age Pomeranians – An Evaluation of High-Risk Populations - Torsten Mundt, DDS; Christian Schwahn, PhD; Florian Mack, DDS, PhD; Ines Polzer, DDS; (Blackwell Synergy, 2007)
The goal of this study was to examine whether psychosocial conditions for general health described in the public health literature are also reflected in tooth loss.